Key Factors Affecting the Success of Construction Multi Project Management: A Case Study of PT X - Budiman, Arief; Wiguna, I Putu Artama (Monas: Jurnal Inovasi Aparatur, 2024)
Simultaneous management of multiple projects has become a trend in the field of energy, oil and gas construction project management over the past decade. This situation is driven by the high market demand and need for fossil fuels, which also stresses project management discipline to improve its performance and efficiency in managing multiple projects simultaneously. Nevertheless, concurrent execution of multiple construction projects often leads to stretched the project durations and cost due to suboptimal resource management, which may become a boomerang and increase project costs. The objective of this study is to identify factors and indicators that contribute to the successful management of multiple projects. Although multi-project management has been extensively studied, there is still a dearth of studies analyzing the elements that make construction multi-project management successful, particularly in the energy, oil, and gas sectors. This research is a case study of an EPCIC company that uses multi-project management and operates in the oil and gas sector. Through purposive sampling techniques, a total of 58 executives from national oil and gas contractors with significant work experience participated in this study through a questionnaire survey. The PLS-SEM approach has revealed that the positive predictor factors influencing the success/performance of multi-project management are resource allocation, teamwork quality, multi-project management competency, and project manager assignment. Flexible and intelligent resource allocation management in multi-project cycles affected by uncertainty is a critical factor.